Value-Added Tax : Administrative and Policy Issues - Tait, Alan. (Washington, D.C. : International Monetary Fund, 1991)
More than 50 countries worldwide employ a value-added tax. What are its effects on prices, exports, and investment? Is it regressive? These and other questions are answered in this collection of papers presented at a March 1990 Jakarta seminar on the VAT in Asia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet